Dynarrestin, a Novel Inhibitor of Cytoplasmic Dynein. Issue 4 (19th April 2018) - Höing, Susanne; Yeh, Ting-Yu; Baumann, Matthias; Martinez, Nancy E.; Habenberger, Peter; Kremer, Lea; Drexler, Hannes C.A.; Küchler, Philipp; Reinhardt, Peter; Choidas, Axel; Zischinsky, Mia-Lisa; Zischinsky, Gunther; et al.
Summary: Aberrant hedgehog (Hh) signaling contributes to the pathogenesis of multiple cancers. Available inhibitors target Smoothened (Smo), which can acquire mutations causing drug resistance. Thus, compounds that inhibit Hh signaling downstream of Smo are urgently needed. We identified dynarrestin, a novel inhibitor of cytoplasmic dyneins 1 and 2. Dynarrestin acts reversibly to inhibit cytoplasmic dynein 1-dependent microtubule binding and motility in vitro without affecting ATP hydrolysis. It rapidly and reversibly inhibits endosome movement in living cells and perturbs mitosis by inducing spindle misorientation and pseudoprometaphase delay. Dynarrestin reversibly inhibits cytoplasmic dynein 2-dependent intraflagellar transport (IFT) of the cargo IFT88 and flux of Smo within cilia without interfering with ciliogenesis and suppresses Hh-dependent proliferation of neuronal precursors and tumor cells. As such, dynarrestin is a valuable tool for probing cytoplasmic dynein-dependent cellular processes and a promising compound for medicinal chemistry programs aimed at development of anti-cancer drugs. Graphical Abstract: Highlights: Dynarrestin inhibits the Hedgehog-signaling pathway downstream of SUFU 125 nM dynarrestin is sufficient to inhibit ciliary transport Specific inhibition of dynein in a novel manner independent of ATP hydrolysis Dynarrestin inhibits proliferation of primary tumor cells Abstract : Höing, Yeh et al. identify dynarrestin, a novel inhibitor of the Hedgehog-signaling pathway. Dynarrestin specifically inhibits dynein in a reversible and novel manner.